Study of the effectiveness of complex terpathy with anti-inflammatory gel «Perio-Aid» in the complex therapy of patients with generalized periodontitis before orthodontic treatment - Ісакова , Наталія Михайлівна; Закалата , Тетяна Ростиславівна; Прокопчук , Зоя Миколаївна (Actual Dentistry, 2021)
Summary. This article investigates the effectiveness and comparative assessment of the effect of gel and rinse aid «Perio-Aid» microflora of periodontal pockets, periodontal tissue and prevention of recurrence of inflammatory processes in the periodontium in young people before orthodontic treatment. It was found that Perio-Aid has more pronounced anti-inflammatory and antimicrobial properties compared to other by means of local therapy. According to the data of clinical and microbiological studies, it has been established that the use of Perio-Aid is already in the tenth day leads to a decrease in the number of periodontal pathogenic microorganisms, eliminates the symptoms of inflammation, reduces the depth of periodontal pockets and has a positive effect on the course of the initial generalized periodontitis, which shortens the preparation time for orthodontic treatment. Key words: periodontium-pathogenic microorganisms, generalized periodontitis.